2005
DOI: 10.1016/j.obhdp.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two tiny giants or two huge dwarfs? Preference reversals owing to number size framing

Abstract: Previous research has found that changes in irrelevant information, evaluation scales, or evaluation modes can lead to preference reversals. Drawing upon prospect theory, we introduced number size preference reversals, which occur under two conditions sharing identical information, evaluation mode, and evaluation scale. That is, for multiple options that have tradeoffs between attributes, an option is favored more when its superior attribute is framed with small numbers than when it is framed with large number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
0
34
0
2
Order By: Relevance
“…observed that there is little difference in our evaluation of a 1 in 10,000 and a 1 in 10,000,000 chance of winning the lottery . Wong and Kwong also revealed that individuals place a higher value on an attribute that differentiates two alternatives when it is framed with small numbers (e.g., sound quality of 0.003% vs. 0.01%, in which the values indicate the percentage of noise in signal) rather than large numbers (e.g., sound quality of 99.997% vs. 99.99%, in which the values indicate the percentage of 1—[noise in signal]) . Similarly, prospect theory accounts for the fact that individuals tend to over‐ or underweight low or high probabilities and to weight losses more heavily than gains .…”
Section: Introductionmentioning
confidence: 78%
“…observed that there is little difference in our evaluation of a 1 in 10,000 and a 1 in 10,000,000 chance of winning the lottery . Wong and Kwong also revealed that individuals place a higher value on an attribute that differentiates two alternatives when it is framed with small numbers (e.g., sound quality of 0.003% vs. 0.01%, in which the values indicate the percentage of noise in signal) rather than large numbers (e.g., sound quality of 99.997% vs. 99.99%, in which the values indicate the percentage of 1—[noise in signal]) . Similarly, prospect theory accounts for the fact that individuals tend to over‐ or underweight low or high probabilities and to weight losses more heavily than gains .…”
Section: Introductionmentioning
confidence: 78%
“…Wong and Kwong (2005) HiFi systems, compact disk changers, job candidates for a computer programming job, airline travel.…”
mentioning
confidence: 99%
“…There are relatively fewer studies that apply this theory to riskless decision making (e.g. Kahneman et al, 1990;Highhouse, 1996;Wong and Kwong, 2005;Bonaccio and Reeve, 2006;Huber et al, 2008). As far as we know, there are no studies similar to ours in that they test whether prospect theory can explain riskless choice in decision tasks based on real offers from an actual company (although Bonaccio and Reeve, 2006 also use quite realistic decision scenarios).…”
Section: Introductionmentioning
confidence: 82%